Management Priorities of Audiovisual Student Projects during the COVID-crisis - Goian, Vita; Goian, Oles; Biletska, Tetiana (International Journal of Emerging Technologies in Learning (iJET), 2021)
COVID-crisis has made significant changes in the educational process of many coun-tries, including the need for new management decisions that would solve the complex problem of accelerating the development of online resources for distance learning. Management, particularly in education, is valuable when it is able to combine both general and specific goals. Especially when it comes to a specific educational process for training future TV and radio journalists, advertisers and PR-managers, screenwrit-ers and directors, sound directors, TV presenters, film and cameramen. The peculiarity of these professions is the combination of both creative and technological components of production and placement of professional audio-video content, i.e. content pro-duced by TV and radio companies, film or TV studios, advertising agencies, and aimed at a mass audience. One of the basic priorities in training such specialists is, first of all, the practice, which is based on the planned implementation of educational audiovisual projects and the ability to put them into effect in certain circumstances, including COVID-crisis caused by COVID-19 virus. Therefore, the aim of the article is to hypothesize how to build a productive distance educational strategy in the condi-tions of COVID-crisis, which specifically affected the quality of practical training of specialists in the field of audiovisual media and arts in Ukraine.